Cold readings made easy - Autore, Bert; Educational Video Network, Inc.; Landshark Films, Inc. (Huntsville, TX : Educational Video Network, 1991)
Noelle C. Nelson coaches actors on how to do a good audition, meaning a good'cold reading', which is critical in getting an acting job. He takes one through beggining, intermediate and advanced levels of cold reading training in order to enable actors to get the part
Lacks personal production credits
Title from title screen
Executive producer, Noelle C. Nelson ; director of photography, Jock Peterson ; editor, Brian Gorne ; camera opertion, Guy Guttman, Tom Mc Carty, Alan Hill ; sound, Michael Landis
Host: Noelle C. Nelson
Keywords: Acting -- auditions; Acting; Career advancement; Employment